A "soft law" szerepéről egy környezetjogi szabályozási terület példáján keresztül - Tahyné Kovács Ágnes (IUSTUM AEQUUM SALUTARE, 2018)
Genetically modified organisms (GMOs) are living organisms whose genetic material has been artificially manipulated in a laboratory through genetic engineering. This creates combinations of plant, animal, bacteria and virus genes that do not occur in nature or through traditional crossbreeding methods. Despite promises from the biotech industry, there is no evidence that any of the GMOs currently on the market offer increased yield, drought tolerance, enhanced nutrition, or any other consumer benefit. Globally, there are 300 regions with outright bans on growing GMOs. In the absence of credible independent long-term feeding studies, the safety of GMOs is unknown. GMOs impact on the environment is significant. The expansion in the production, distribution and consumption of GMOs, has produced discussions about pros and cons concerning their legal regulation. Efforts to regulate genetically modified organisms have taken place at both international and regional levels. At the international level, the Cartagena Protocol on Biosafety, based on the precautionary principle, is one of the first legally binding international agreements to regulate the transboundary transfer of GMOs. The inclusion of the precautionary principle in the GMO controversy has engendered even more debate, especially in the area of the state’s right of decision. This principle relies on anticipatory action in the absence of firm scientific evidence. While this principle has the potential to protect the environment from the uncontrolled spread of GMOS, it has been trapped in an endless debate over its application and compatibility with existings laws. In order to restrict or prohibit the cultivation of GMOs, some Member States had recourse to the safeguard clauses and emergency measures pursuant to Article 23 of Directive 2001/18/EC and Article 34 of Regulation (EC) No. 1829/2003 as a result of which, depending on the cases, new or additional information made available since the date of the consent and affecting the environmental risk assessment. Other Member States have made use of the notification procedure set out in Article 114(5) and (6) TFEU which requires putting forward new scientific evidence relating to the protection of the environment or the working environment. In addition, the decision-making process has proved to be particularly difficult as regards the cultivation of GMOs in light of the expression of national concerns which do not only relate to issues associated with the safety of GMOs for health or the environment. In that context, it appears appropriate to grant Member States, in accordance with the principle of subsidiarity, more flexibility to decide whether or not they wish to allow the cultivation of GMOs on their territory without affecting the risk assessment provided in the system of Union authorisations of GMOs, either in the course of the authorisation procedure or thereafter, and independently of the measures that Member States cultivating GMOs are entitled or required to take by application of Directive 2001/18/EC to avoid the unintended presence of GMOs in other products. The grant of that possibility to Member States is likely to improve the process for authorisation of GMOs and, at the same time, is also likely to ensure freedom of choice for consumers, farmers and operators whilst providing greater clarity to affected stakeholders concerning the cultivation of GMOs in the European Union. This Directive should therefore facilitate the smooth functioning of the internal market. The EU has given governments more power to decide whether to plant genetically modified crops, which are highly restricted in Europe. In 2015, he European Parliament has passed a new law giving states more flexibility by a large majority. The author of this study introduces a long regulatory path from the soft law rules of GMO-free regions to the current EU directive.